Effects of Salinity and Temperature on Long-Term Survival of the Eel Pathogen Vibrio vulnificus Biotype 2 (Serovar E) - Marco-Noales, Ester (American Society for Microbiology, 1999)
Vibrio vulnificus biotype 2 (serovar E) is a primary eel pathogen. In this study, we performed long-term survival experiments to investigate whether the aquatic ecosystem can be a reservoir for this bacterium. We have used microcosms containing water of different salinities (ranging from 0.3 to 3.8%) maintained at three temperatures (12, 25, and 30°C). Temperature and salinity significantly affected long-term survival: (i) the optimal salinity for survival was 1.5%; (ii) lower salinities reduced survival, although they were nonlethal; and (ii) the optimal temperature for survival was dependent on the salinity (25°C for microcosms at 0.3 and 0.5% and 12°C for microcosms at 1.5 to 3.8%). In the absence of salts, culturability dropped to zero in a few days, without evidence of cellular lysis. Under optimal conditions of salinity and temperature, the bacterium was able to survive in the free-living form for at least 3 years. The presence of a capsule on the bacterial cell seemed to confer an advantage, since the long-term survival rate of opaque variants was significantly higher than that of translucent ones. Long-term-starved cells maintained their infectivity for eels (as determined by both intraperitoneal and immersion challenges) and mice. Examination under the microscope showed that (i) the capsule was maintained, (ii) the cell size decreased, (iii) the rod shape changed to coccuslike along the time of starvation, and (iv) membrane vesicles and extracellular material were occasionally produced. In conclusion, V. vulnificus biotype 2 follows a survival strategy similar to that of biotype 1 of this species in response to starvation conditions in water. Moreover, the aquatic ecosystem is one of its reservoirs.